The Potential of Dadih as a Functional Food in Disaster Preparedness - Gusnedi; Habibi, Nur Ahmad; Sartika, Wiwi; Ismanilda; Amalia, Suci (proceedinginternational, 2024)
Dadih is a traditional food from West Sumatra made through a 48-hour fermentation process in bamboo. It exhibits a diverse range of nutritional content and active compounds. This research aimed to evaluate dadih from Padang Panjang as a potential functional food for emergency situations. The method involved testing dadih to determine its nutritional content, antioxidant activity, and shelf life. The research results indicated that dadih has a relatively good protein content at 7.55% and an antioxidant activity of 142.49±0.25 mg/kg, falling into the moderate category. Furthermore, dadih boasts an excellent shelf life, lasting up to 6 days at room temperature and 30 days in the refrigerator. In conclusion, based on its nutritional content, antioxidant activity, and shelf life, dadih is considered a suitable candidate for a functional food in emergency conditions.